2019
DOI: 10.3390/f10060500
|View full text |Cite
|
Sign up to set email alerts
|

Primary and Secondary Branch Growth in Black Spruce and Balsam Fir after Careful Logging around Small Merchantable Stems (CLASS)

Abstract: Careful logging around small merchantable stems (CLASS) is a partial cutting treatment that consists of the harvest of 70%–90% of the merchantable volume of an irregular coniferous stand. In this treatment, regeneration, saplings and small merchantable stems (DBH < 15 cm) are preserved and can continue to grow and develop into the dominant layer of the new stand. The aim of this project was to examine the effects of CLASS on the primary and secondary growth of branches, as well as on branch diameter in blac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Moreover, black spruce has a very slow growth rate, especially for older individuals [2]. Thus, even if branches of our sampled trees increased their growth after treatment, as was observed in other studies [15,44], this increase was so small that the effect was minimal at the time of our sampling. The most important effect will likely be branch longevity, as lower branches may remain alive longer [45].…”
Section: Generalized Additive Modelmentioning
confidence: 60%
See 2 more Smart Citations
“…Moreover, black spruce has a very slow growth rate, especially for older individuals [2]. Thus, even if branches of our sampled trees increased their growth after treatment, as was observed in other studies [15,44], this increase was so small that the effect was minimal at the time of our sampling. The most important effect will likely be branch longevity, as lower branches may remain alive longer [45].…”
Section: Generalized Additive Modelmentioning
confidence: 60%
“…We divided crown length into five sections, each having 20% of the total crown length, and we collected at least three whorls from each of these five sections, as in Lemay, Krause, and Achim [15]. The relative height of a branch in the live crown was determined as follows:…”
Section: Branch Diameter Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…), Goudiaby et al [43] also detected a positive correlation between stem volume growth, growth efficiency (stem to foliage biomass ratio), and foliage biomass at mid-crown. However, for shade-tolerant species such as black spruce, opening the canopy may not necessarily affect branch development, taper, or stem shape in the same way [49]. Thus, Goudiaby et al [43] again observed no change in growth efficiency, foliage biomass, or biomass density after thinning.…”
Section: Wood Allocation and Stem Shape Variations Following Treatmentmentioning
confidence: 99%
“…Ever since theories related to stem form were first proposed [45], foresters have concurred that silvicultural practices favoring growth increment also produce changes in stem shape. Various authors have suggested that the patterns of wood deposition along the stem are affected by variations in crown size, which in turn are affected by tree characteristics and stand conditions (particularly stand density) [46][47][48][49]. This hypothesis has been verified for some species, including Douglas fir and Sitka spruce (Picea sitchensis), for which Mitchell [17] found that basal allocation temporarily increased after thinning, suggesting a period of acclimatized growth during which trees re-equilibrate with post-thinning wind loads.…”
Section: Wood Allocation and Stem Shape Variations Following Treatmentmentioning
confidence: 99%